Leaders' Interpersonal Communication in Improving Graduate Quality at Pondok Pesantren - Zebua, Yusri; Budianti, Yusnaili; Hanum, Azizah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The goal of this study is to discover the Pondok Leaders' Interpersonal Communication Pattern in terms of improving the Quality of Graduates; to understand the Pondok Leaders' Efforts in Effective Interpersonal Communication, and to understand the supporting and inhibiting factors of the Interpersonal Communication process of the Leaders of the Umi Kalsum Islamic Boarding School in Nias. Because this study aims to obtain a description of the data derived from data collection by researchers about the Interpersonal Communication of the Leaders of the Umi Kalsum Islamic Boarding School in Nias in Improving the Quality of Graduates, it employs a qualitative approach with a descriptive method. The data collection technique used interviews, observation, and documentary studies, while the data validity standard proposed by Lincoln and Guba, which consists of credibility, transferability, dependability, and confirmability, was used to strengthen the validity of the data found and the authenticity of the research. -their middle; and Supporting factors for effective interpersonal communication of boarding school leaders as a result of the emergence of a strong sense of belonging and kinship in Islamic boarding schools.